MANAJEMEN KEUANGAN PENDIDIKAN MASA PNDEMI COVID 19 PADA MTs NEGERI 4 SUMEDANG BERDASARKAN RENCANA KEGIATAN ANGGARAN MADRASAH (RKAM) - suprapti, atik; rofiqi, budiyana; rahman, taufik (Journal of Management Review, 2024)
Financial management is one of the determinants of institutional progress, because financial management is closely related to all components of education. Madrasah financial management is implemented so that the education budget can be utilized to finance the procurement of infrastructure, building and yard maintenance, salaries of civil servants or non-permanent employees, employee health insurance, payment of funeral services, the amount of which is determined by applicable laws and regulations. Madrasah finance consists of planning, organizing, implementing/implementing and supervising, but whether the management has been going well. MTs Negeri 4 Sumedang in financial management is regulated in the preparation of the 2019/2020 Madrasah Activity Plan and Budget. This is made in three stages, namely budget planning, budget management and budget reporting which is reported every semester to the Ministry of Religion.